Two new Peperomia (Piperaceae) species from Southern Bahia, Brazil - Monteiro, Daniele; Leitman, Paula; Coelho, Macielle M. (Phytotaxa, 2016)
Two new species of Peperomia of mountain forests from southern Bahia state, P. epipremnifolia and P. sulbahiensis, are described and illustrated. Information on their conservation status, habitat, distribution, phenology, and comments on how to differentiate them from closely related taxa is presented. In addition, an identification key to the species of Peperomia from southern Bahia mountain forests is given.